Improving User Interface Accessibility For Chinese Elderly Tourism Through Service Design In Yancheng, Jiangsu Province, China - Chang, Runyi (2023)
The aging process in China has been accelerating. Since 2020, China has moved from a deeply aging society to a super-aging society. The growing base of population aging inevitably brings about the aging of consumer groups in the market. Especially when elderly people are in tourism, they have more available time, lower financial pressures, and considerable purchasing power, so elderly tourism is becoming an integral segment of the tourism industry. Although extensive literature has discussed elderly tourism in China as a separate sector, it has not been able to change the situation of low accessibility. Until now, there has been insufficient research to identify the needs, behaviors, and expectations of elderly people in tourism. As a result, the traveling experience of Chinese elderly people is unsatisfactory since the tourism industry cannot accurately match the demands of the elderly in terms of products, services, and travel processes. In this study, the author applied service design as an interdisciplinary approach to improving accessibility to elderly tourism. Using a combination of quantitative and qualitative methods, including Pearson correlation, multiple linear regression, and interview verification. The author explored a range of factors that influence traveling experience of elderly people throughout journeys.